1990
DOI: 10.1139/v90-237
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of iron-catalysed hydrogen peroxide decomposition by magnesium

Abstract: Catalytic decomposition of alkaline hydrogen peroxide by iron can be retarded by introduction of magnesium ions. This effect has been studied to evaluate the possibility of stabilization via formation of an iron–magnesium complex species. Under alkaline conditions, magnesium reacts with initial hydrolysis products of Fe3+ to produce a colourless complex species, in which the metal centres are probably linked through oxy or hydroxy bridges. This species is produced when the Mg:Fe molar ratio exceeds 6:1, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Agnemo and Gellerstedt (1979) found an energy of activation of 68 kJ/mol at pH 10.5. Even with the small variation in pH, values from Abbot and Brown (1990) and Hobbs and Abbot (1994) were fairly close to the regression line; the value from Agnemo and Gellerstedt (1979) was not as close. The generally good agreement of the data from different sources, however, lead us to conclude that the procedures used were adequate for the relative comparisons being made in this work.…”
Section: Discussionmentioning
confidence: 75%
“…Agnemo and Gellerstedt (1979) found an energy of activation of 68 kJ/mol at pH 10.5. Even with the small variation in pH, values from Abbot and Brown (1990) and Hobbs and Abbot (1994) were fairly close to the regression line; the value from Agnemo and Gellerstedt (1979) was not as close. The generally good agreement of the data from different sources, however, lead us to conclude that the procedures used were adequate for the relative comparisons being made in this work.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, since Mn is the most critical metal ion for hydrogen peroxide decomposition (Lapierre , priority must be given to its removal. Simulation also evidences that MGDA complexes a high amount of Mg, which might be another disadvantage, because the presence of Mg in the pulp might be beneficial in the peroxide stage (Colodette et al 1989;Abbot and Brown 1990). A pH between 6.5 and 7 was defined to proceed to the experimental tests.…”
Section: Computer Chemical Simulationsmentioning
confidence: 99%
“…These metals are in the process as impurities of chemicals used in the bleaching, washing waters and wood itself and the control of its presence is very important to minimize hydrogen peroxide degradation and maximize bleaching efficiency (Wuorimaa et al 2006). On the other hand, the presence of magnesium (Mg) in the bleaching step is important to stabilize the metal ions that increase peroxide degradation (Colodette et al 1989;Abbot and Brown 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, except run 9, the composition of the monosaccharides was, within error, identical with the one from the standard reaction, run 1. Only the chromic acid oxidized cellulose yielded an excess of 0.8 mole% mannose, which must result from keto group formation at C-2 of an anhydroglucose unit of the cellulose chain: (Samuelson 1983;Burton and Campbell 1985;Abbot and Brown 1990). In preliminary experiments it was found that ferrous sulfate alone also speeds up the hydrolysis of cellulose.…”
Section: Kinetics Of Oxidation By Iodometrymentioning
confidence: 99%